The story of Peppa Pig. - Astley, Neville; Baker, Mark, 1959- (New York, NY : Scholastic Inc., 2012)
Peppa Pig and her family visit Granny and Grandpa Pig.
"This book is based on the TV series Peppa Pig. Peppa Pig is created by Neville Astley and Mark Baker"--Page facing t.p.
4.5
Preschool.
Preschool
Keywords: Families -- Juvenile fiction; Peppa Pig (Fictitious character) -- Juvenile fiction; Swine -- Juvenile fiction; Family life -- Fiction; Peppa Pig (Fictitious character) -- Fiction; Pigs -- Fiction; Family life -- Fiction; Peppa Pig (Fictional character) -- Fiction; Pigs -- Fiction; Radio and television novels; Picture books for children; Radio and television novels